Unarmed and dangerous: patterns of threats by citizens during deadly force encounters with police - Shane, Jon (Routledge focus, 2019)
Cover; Title; Copyright; Contents; Preface; Foreword; Acknowledgments; 1 Introduction; 2 Focal Concerns of Police Officers and the Legal Framework; 3 National Police Use of Force Data; 4 Data Analysis and Results; 5 Discussion of the Findings and Policy Implications; References; Index